Children's academic achievement and goal orientations: does the ethnic membership matter? / Rendimiento académico y orientación a las metas: el papel de la etnicidad. Issue 4 (2nd October 2017) - Diaconu-Gherasim, Loredana R.; Iacob, Luminita M.; Gavreliuc, Alin
Abstract: This study explored how ethnic membership relates to children's academic achievement and goal orientations and whether there are ethnic differences in how goal orientations are linked to academic achievement. Further, we investigated whether these relations vary based on the geographical region where ethnic groups live. The sample included 361 children (179 girls), age 12–15 years, from two regions in Romania, Banat ( n  = 237) and Moldavia ( n  = 124). Ethnic differences in academic achievement were found only between majority and Hungarian minority ethnic groups who live in different areas, whereas ethnic differences in goal orientations were found between minority and both groups of majority children (living in the same and in different geographical regions). The strengths of the associations between goals and academic achievement were not significantly different based on ethnic and regional background. The findings highlight the importance of cultural (i.e., ethnicity) and contextual (i.e., regional area) factors in relation to children's achievement and motivation (i.e., goal orientations). Additionally, our findings show that the relations between academic achievement and goal orientations are similar across the analysed ethnic and regional groups.